Antibacterial effect of the leaf extracts of Ficus thonningii on Escherichia coli and Staphylococcus aureus in Kebbi State, Northern Nigeria - Galadima, Musa (International Journal of Pharmaceutical & Biological Archive, 2021)
The use of ethnomedicinal plants in the treatment of many ailments is very popular in the developing world. Ficus thonningii, commonly called the wild fig, has been used in numerous communities in Nigeria as an ethnomedicinal regimen. The phytochemical and antibacterial activities of the plant were carried out in this study. The aqueous extract of the leaves of F. thonningii was screened for antibacterial activity carried out by disc diffusion method while the minimum inhibitory concentrations and the minimum bactericidal concentrations were determined using broth dilution method. Phytochemical constituents present in the extract were alkaloids, tannins, flavonoids, anthraquinones, saponins, phlobatannins, and resins. In this analysis, the leave extracts inhibited the growth of test organisms at all concentration (30, 60, and 90 mg/ml) although with significant differences. The larger zone of inhibition was observed on Staphylococcus aureus which signifies that it is more susceptible to the leaves extract compared to Escherichia coli. The high antibacterial activity of the extract recorded on E. coli and S. aureus was encouraging at 90 mg/ml with inhibition zone of 3.9 Â± 0.33 and 4.4 Â± 0.26. The antibacterial activity of the extract was also compared with that of ciprofloxacin. This could be due to the secondary metabolites present in F. thonningii, it has been well documented that they possess significant antimicrobial activities that could invariably be useful in the development of safe chemotherapeutic agents for the treatment of many bacterial infections.